The amulet: A novel - Craddock, Charles Egbert, 1850-1922 (Salt Lake City, UT : Project Gutenberg, 2022)
"The Amulet" by Charles Egbert Craddock is a novel written in the early 20th century. The story unfolds against the backdrop of the American frontier during the aftermath of the Seven Years' War. The narrative introduces Captain Howard and his daughter, Arabella, as they navigate their life at Fort Prince George, embodying a dynamic mix of isolation, the perils of military life, and burgeoning cultural encounters with Native Americans. The opening of the novel paints a vivid picture of Fort Prince George on a bleak, moonlit night, capturing Arabella's fascination with the stark beauty surrounding her. It describes her interactions with the men stationed at the fort, including Captain-Lieutenant George Mervyn, whom she finds somewhat lacking in charm, and Ensign Raymond, who evokes her sympathy. As a sense of unease develops between the young men, hints of underlying tensions are suggested, amidst contrasts of military duty and domestic life. The interactions set a stage rich in character development, hinting at themes of love, social status, and the complexities of life on the untamed frontier. (This is an automatically generated summary.)
Release date is 2022-12-06
Peter Becker, David E. Brown, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: South Carolina -- History -- Colonial period, ca. 1600-1775 -- Fiction; Cherokee Indians -- Fiction; Fort Prince George (S.C.) -- Fiction